Magnetization of NixCu₂-xMnSn - MacDonald, Richard A. (My University, 1976)
The magnetization of the Heusler alloys NixCu₂-xMnSn has been measured. These alloys, of the form X₂YZ, have been investigated in order to determine the X site dependence of the interactions which are responsible for the ferromagnetism. It is seen that the Curie temperatures vary nonlinearly with composition suggesting that the short range interactions which determine them vary in a similar manner. Saturation moments are found to remain constant; however, a decrease in paramagnetic moment as the copper concentration is increased, is attributed to disorder.
Keywords: Physics; Physics